β-Glucuronidase Pattern Predicted From Gut Metagenomes Indicates Potentially Diversified Pharmacomicrobiomics - Candeliere, Francesco; Raimondi, Stefano; Ranieri, Raffaella; Musmeci, Eliana; Zambon, Alfonso; Amaretti, Alberto; Rossi, Maddalena (Frontiers in Microbiology, 2022)
β-glucuronidases (GUS) of intestinal bacteria remove glucuronic acid from glucoronides, reversing Phase II metabolism of the liver and affecting the level of active deconjugated metabolites deriving from drugs or xenobiotics. 279 non-redundant GUS sequences are known in the gut microbiota, classified in 7 structural categories (NL, L1, L2, mL1, mL2, mL1,2, and NC) with different biocatalytic properties. In the present study, the intestinal metagenome of 60 healthy subjects from five geographically different cohorts were assembled, binned, and mined to determine qualitative and quantitative differences in GUS profile, potentially affecting response to drugs and xenobiotics. Each metagenome harbored 4 to 70 different GUS, altogether accounting for 218. The amount of intestinal bacteria with at least one GUS gene was highly variable, from 0.7% to 82.2%, 25.7% on average. No significant difference among cohorts could be identified, except for ETH cohort where GUS encoding bacteria were significantly less abundant. The structural categories were differently distributed among the metagenomes, but without any statistical significance related to the cohorts. GUS profiles were generally dominated by category NL, followed by mL1, L2, and L1. The GUS categories most involved in the hydrolysis of small molecules, including drugs, are L1 and mL1. Bacteria contributing to these categories belonged to Bacteroides ovatus, Bacteroides dorei, Bacteroides fragilis, E. coli, Eubacterium eligens, F. prausnitzii, Parabacteroides merdae, and Ruminococcus gnavus. Bacteria harboring L1 GUS were generally scarcely abundant (< 1.3%), except in 3 metagenomes, where they reached up to 24.3% for the contribution of Escherichia coli and Faecalibacerium prausnitzii. Bacteria harboring mL1 GUS were significantly more abundant (mean = 4.6%), with Bacteroides representing a major contributor. Albeit mL1 enzymes are less active than L1 ones, Bacteroides likely plays a pivotal role in the deglucuronidation, due to its remarkable abundance in the microbiomes. The observed broad interindividual heterogeneity of GUS profiles, particularly of L1 and mL1 categories, likely represent a major driver of pharmacomicrobiomics variability, affecting drug response and toxicity. Different geographical origins, genetic, nutritional, and lifestyle features of the hosts seemed not to be relevant in the definition of glucuronidase activity, albeit they influenced the richness of the GUS profile.